Penerapan Terapi Rendam Kaki Dengan Air Hangat Pada Penderita Hipertensi Di Wilayah Kerja Puskesmas Tanah Tinggi - Kasmiana; Fadhli, Rohmi; Putri, Mersi Eka; Rahmaniza (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: To analyze the effect of the application of warm water foot soak therapy on blood pressure in hypertension patients in the Tanah Tinggi Health Center work area. Methods: This study used a quasi-experimental design by providing warm water foot soak therapy as an intervention. Blood pressure was measured before and after the intervention to assess its effect. The sampling method was non-probability sampling with a total sampling approach, involving 27 respondents. Because the data was not normally distributed, statistical analysis was carried out using the Wilcoxon test with a significance level of ρ < 0.05. Results: The Wilcoxon test results showed a significance value of ρ = 0.000, which means ρ < 0.05. Therefore, the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected. This indicates that there is a significant effect of warm water foot soak therapy in lowering blood pressure among hypertension patients. Conclusion: Warm water foot soak therapy has a significant effect on reducing blood pressure and can be used as a non-pharmacological method for managing hypertension in the Tanah Tinggi Health Center work area.